Immunotherapy in Metastatic Mucosal Melanoma with Disseminated Intravascular Coagulation: A Case of Success. (8th October 2021) - Luna Pais, Helena; Luz, Paulo; Lobo-Martins, Soraia; Mansinho, André; Sousa, Rita; Luís, Rita; Presa, Dolores; Gomes, Daniel; Costa, Luís; Teixeira de Sousa, Rita
Abstract : Mucosal melanoma accounts for 1% of all melanomas. It is more aggressive than cutaneous melanoma, and local excision provides the best disease-free survival. The vast majority of patients eventually develop metastases, with a metastatic pattern independent of the primary tumor site. While studies show that BRAF and KIT inhibitors have a role in the management of these patients, the actual treatment focus is on immunotherapy. Herein is described the case of a 79-year-old woman with metastatic mucosal melanoma and bone marrow infiltration causing disseminated intravascular coagulation, who was treated with an immunotherapy combination (anti-CTLA-4 and anti-PD-1 antibodies), achieving complete disease remission. This is the third case of melanoma with disseminated intravascular coagulation at presentation and the second case treated with immunotherapy in the literature, but the only one achieving disease remission.